2015
DOI: 10.4314/mcd.v9i2.4
|View full text |Cite
|
Sign up to set email alerts
|

Socio - ecological analysis of natural resource use in Betampona Strict Natural Reserve

Abstract: Without an adequate understanding of the socio-political context in which a natural environment is embedded, it is impossible to prevent, mitigate and adapt to future unwanted changes in the socio-ecological system. It is advantageous for environmental managers to see the social aspects of the socio-ecological system so that they can understand not only the effects but also the motivations of natural resource use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 25 publications
(27 reference statements)
2
17
0
Order By: Relevance
“…Those surveyed ate 6,726 forest animals (mean of 7 mammals and 10 birds per household), or ∼3.27 kg of wild meat per person (4.48 kg per adult equivalent) during the prior year. This amount of wildlife is much higher than that reported in other regions of Madagascar including Kianjavato (Borgerson et al, 2018a), Alaotra (Borgerson et al, 2018b), and Betampona (Golden et al, 2014b), but it is similar to that reported in nearby Makira (Golden et al, 2014a;Brook et al, 2019), and far less than the amount eaten in the Amazon and Congo basins (63 and 51 kg/capita/year, respectively; Nasi et al, 2011). Further, as much as 75% of all meat eaten in some communities was from forest animals.…”
Section: Discussionsupporting
confidence: 49%
“…Those surveyed ate 6,726 forest animals (mean of 7 mammals and 10 birds per household), or ∼3.27 kg of wild meat per person (4.48 kg per adult equivalent) during the prior year. This amount of wildlife is much higher than that reported in other regions of Madagascar including Kianjavato (Borgerson et al, 2018a), Alaotra (Borgerson et al, 2018b), and Betampona (Golden et al, 2014b), but it is similar to that reported in nearby Makira (Golden et al, 2014a;Brook et al, 2019), and far less than the amount eaten in the Amazon and Congo basins (63 and 51 kg/capita/year, respectively; Nasi et al, 2011). Further, as much as 75% of all meat eaten in some communities was from forest animals.…”
Section: Discussionsupporting
confidence: 49%
“…While chicken has potential to replace wildlife nutritionally, raising domestic chicken flocks in remote, rural communities in Madagascar is a complex endeavor. Primarily, chicken has not served as a consistent and economical source of food in many parts of Madagascar because community poultry flocks are vulnerable to Newcastle disease (1012). Newcastle disease is a virus that causes neurological, respiratory, and gastrointestinal symptoms in poultry (13), and is often fatal, hence preventing the stable establishment of productive chicken flocks.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of deforestation extends well beyond habitat loss through the unleashing of secondary factors that, alone or in combination, further erode the viability of already vulnerable populations. For example, shrinking and degraded habitats increase opportunities for hunters, pathogens and invasive species to prey upon, infect or out-compete resident populations while species unable to disperse between fragmented habitats can suffer from inbreeding depression [16][17][18][19]. Together, these factors may have dramatically outpaced the effects of climate change.…”
Section: Introductionmentioning
confidence: 99%
“…In the early 1990s, Madagascar National Parks developed a collaboration with the conservation non-governmental organization (NGO), Madagascar Fauna and Flora Group (MFG), to serve as their research partner. The presence of a research team in the forest and the development of positive relationships and programs with community members have greatly reduced infractions, especially when compared to other sites [18]. Although the MFG's programs have lessened the likelihood of fires entering BNR, the environmental repercussions of previous fires now represent the greatest threat to its biodiversity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation